Microwave-assisted organic synthesis of pyrroles (Review) - Emilio Mateev; Ali Irfan; Alexandrina Mateeva; Maya Georgieva; Alexander Zlatkov (Pensoft Publishers, 2024)
The detection of pyrrole rings in numerous organic compounds with various pharmacological activities, emphasizes its huge importance in medicinal chemistry. Thus, the synthesis of pyrroles continues to arouse interest and Paal-Knorr condensation is considered to be the main synthetic route. A significant advance has been made since the MW activation was introduced in the organic synthesis which can be confirmed with the rapid growth of the published papers on that topic. Microwave irradiation is gaining popularity since faster reaction time, higher yields, easier work-up and reduced energy input can be achieved. Furthermore, it appears in numerous green chemistry protocols. The aim of the current article was to provide insights into the microwave syntheses of pyrrole derivatives, focusing on the most used synthetic approaches - Paal-Knorr, Clauson-Kaas, Barton-Zard, Hantzsch and others. The article was divided into several sections starting with the principles of the microwave organic synthesis. Thereafter the structure and the main pharmacological effects of the pyrrole derivatives were examined. Subsequently, articles describing the synthesis of pyrroles via Paal-Knorr, Hantzsch, Clauson-Kaas and Barton- Zard were discussed. All the reviewed papers conclude a significant reduction of the reaction times after MW irradiation compared to conventional heating.